Critical storytelling in millennial times : undergraduates share their stories of struggle - Braniger, Carmella J.; Jacoby, Kaytlin M. (Brill Sense, 2019)
Critical stories are more than just anecdotes or tales. They are narratives that raconter, or recount, the author's own experiences, situating them in broader cultural contexts. Just as the autoethnographer situates the self in relation to the "others" of which the self is both a part and from which it is distinct, the critical storyteller situates his or her story of conflict in relation to the broader reality from which the conflict arises. The key is the reality that is being related and the perspective from which it is being shared. In 'Critical Storytelling in Millennial Times', marginalized, excluded, and oppressed people share insights from their liminality and help readers learn from their perspectives and experiences. Examples of stories in this volume range from undergraduate perspectives on financial aid for college students, to narratives on first-hand police brutality, to heartbreaking tales about addiction, bullying, and the child sex trade in Cambodia. Undergraduate authors relate their stories and pose important questions to the reader about inciting change for the future. Follow along in their journeys and learn what you can do to make a change in your own reality.
Keywords: College students -- United States -- Social conditions.; College students -- United States -- Attitudes.; College students -- United States -- Biography.; Minority college students -- United States.; Women college students -- United States.; Generation Y.; Generation Z.; Étudiants -- États-Unis -- Conditions sociales.; Étudiants -- États-Unis -- Attitudes.; Étudiants -- États-Unis -- Biographies.; Étudiantes -- États-Unis.; Génération Internet.; Génération Z.; EDUCATION -- Higher.; Women college students; Minority college students; Generation Z; Generation Y; College students -- Social conditions; College students; College students -- Attitudes; Discrimination in higher education; United States; Biographies